Cities of the dead: approaching the lost landscape of Hellenistic and Roman necropoleis of Cyprus - Lysandrou, Vasiliki; Agapiou, Athos (My University, 2016)
An analytic approach of the numerous but poorly documented Hellenistic and Roman necropoleis of Cyprus, excavated or simply spotted through the years, is presented in this paper. Geographical Information Systems (GIS) were used so as to better understand the lost landscape of the Hellenistic and Roman necropoleis. GIS were applied to visualize, rationalize, and analyze the vast quantity of material, starting from the simple site location of the known Hellenistic and Roman cemeteries, proceeding with an analytic approach of the available scarce information, to reveal eventually specific spatial patterns. Initially, indexing, registration, topographic documentation, and mapping linked with all the necessary information of the known necropoleis were accomplished. In addition, spatial analysis considering environmental and other parameters in GIS was carried out in a macroscale perspective. The above analysis resulted notable aspects related to the lost funerary landscape of ancient Cyprus.
Keywords: Cyprus; GIS; Hellenistic-Roman necropoleis; Lost landscapes; Spatial analysis